BUAH CEMARA INTEGRASI DAN INTERKONEKSITAS SAINS DAN ILMU AGAMA - Azhar Arsyad (State Institute of Islamic Studies (IAIN) Palu, 2011)
Abstract: Human beings possess three kinds of intruments to catch the whole reality. The three instruments are the five senses, reason and intellectuality as well as intuiion (revelation and inspiration) whreas the Western intellectluas agree one instrument only, namely the five senses so that they develope one research method only, namely observation method and experiment. The observation method is continually developed into very sopisticated level but it persistently derive from the sense perception. Reason—in the form of reasoning—is employed, but only to choose, to decide and to perform reasoning, not as other instruments to catch the reality. This makes the Western intellectuals different from the Muslim intellectuals since the later admit the validity of not only the observation method but also of the rational and intuitive method. Kata Kunci: integrasi, interkonektisitas, sains, ilmu agama, panca indera, akal